Implementation of the Cooperative Integrated Reading and Composition (CIRC) Strategy in Improving the Learning Ability of Elementary Students - Arfatussalamah Tanjung (Journal of Contemporary Islamic Primary Education, 2023)
This study aims to determine the application of Cooperative Integrated Reading and Composition (CIRC) learning strategies in improving the learning abilities of elementary age students. The type of research used is qualitative research with descriptive methods that aim to describe, explain and answer questions about phenomena and events that are happening at this time. Based on the research results from the implementation of the Cooperative Integrated Reading and Composition (CIRC) Strategy in improving the learning abilities of MI/SD students that: (1) Based on the results and discussion in this study, it can be concluded that the Cooperative Integrated Reading and Composition (CIRC) learning strategy applied for children of elementary school age it is quite good because it fulfills several indicators, including: (1) students can understand and complete guessing pictures easily, (2) students can present the results of guessing pictures in their own language, (3) students able to work well together.